Pengaruh Wisata Halal Terhadap Kepuasan Wisatawan Dan Dampak Moderasi Religiusitas Di Sumatera Barat - Ramadhan, Sri; Wisanggara, Rangga; Rama, Alfi Syukri; Putri, Tata Asriandara (ITB AAS INDONESIA Surakarta, 2024)
Halal tourism is believed to be one of the factors that influence the satisfaction of Muslim tourists, but the satisfaction of Muslim tourists also depends on the level of religiosity they have. The high or low level of religiosity of a tourist will also have an impact on behavioral intentions towards loyalty related to customer satisfaction. studies on the impact of religiosity are still very limited, therefore religiosity is used as a moderating variable to find answers to the influence of halal tourism on Muslim tourist satisfaction. This study uses a quantitative approach that aims to determine the relationship between variables, the analysis tool uses SEM analysis with the AMOS application. Based on Hypothesis Test Halal tourism has a positive and significant impact on tourist satisfaction. This can be seen from the CR value of 6.276> 1.96 and P value 1.96 with a P value of 0.004